(untitled) (Global Journal of Management and Business Research, 2012)
Research on job satisfaction is replete with the studies exploring the impacts of personal and demographic attributes of the employees on their organizational attitudes. Demographics are tested as the predictor of job satisfaction or dissatisfaction and its consequences like involvement, commitment, absenteeism and turnover. Mixed results have been reported by the researchers showing that different demographic factors play different roles in diverse settings, for example, in advanced and developing countries. Thus, researchers have proved that demographic analysis is indispensable to understand the employee attitudes. This paper is a part of PhD research project on #x2018;job satisfaction of academicians in the HEIs of KPK, Pakistan.#x2019;